Financial Literacy, Capital Structure, and Financial Planning as Determinants of MSME Sustainability: Mediating Role of Profitability - Ulfah Rizky Muslimin; Elia Madatu Tandililing; Putri Ratnasari; Maria Apriyane Patty; Rizka Aisyah Nurjannah (Lembaga Riset dan Inovasi Al-Matani, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Papua face significant sustainability challenges, particularly in the early years of operation, due to limitations in financial management practices. This study examines the direct and indirect effects of financial literacy, capital structure, and financial planning on MSME sustainability, with profitability as a mediating variable. A quantitative explanatory approach was employed using data from 200 MSMEs selected through purposive sampling. The analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that capital structure and financial planning have positive and significant effects on profitability, while financial literacy shows a negative significant effect. Profitability, in turn, has a strong positive influence on sustainability and mediates the relationships between financial variables and MSME sustainability. The findings suggest that, in certain contexts, higher financial literacy may lead to more conservative financial behavior, which can reduce short-term profitability and indirectly affect sustainability outcomes. This study contributes to the literature by providing an integrated model of MSME sustainability and highlighting the context-dependent role of financial literacy. However, the findings should be interpreted with caution due to the use of cross-sectional and self-reported data. The results offer practical implications for policymakers and practitioners in designing financial development programs that balance risk management and profit optimization to support sustainable MSME growth.